PERLINDUNGAN PEMEGANG HAK CIPTA KARYA DESAIN GRAFIS PADA PLATFORM E-COMMERCE MENURUT UNDANG-UNDANG HAK CIPTA - Raihan Muhammad El Rahman (2024)
In the era of digitalization and development of information technology, e-commerce platforms have become one of the largest markets for products and services throughout the world. The presence of increasingly advanced technology makes the opportunities for violations even greater. The aim of this research is to find out, identify, understand and review law enforcement efforts taken by understanding the legal framework for copyright infringement issues. These violations are regulated in Law Number 28 of 2014 concerning Copyright. Legal protection for copyright holders needs to protect their rights because this can harm their economic and moral values. One form of creation that is protected by copyright is graphic design, which is the work of humans in the form of images and writing which has its own meaning. This research will examine the extent to which existing laws protect and guarantee the rights of copyright holders. This research uses qualitative research. The research is normative juridical in nature, namely by collecting data using a library research approach by reviewing and collecting reading sources and legal literature materials. The act of duplicating and modifying a logo is an act of copyright infringement and is categorized as a copyright violation according to Law Number 28 of 2014 concerning Copyright. Creators and Copyright Holders are guaranteed their rights according to statutory regulations, which in this case is Law Number 28 of 2014 concerning Copyright, which explains in detail starting from definitions, regulations, to problem resolution that can be taken. A creator and copyright holder who feels their rights have been violated can file a lawsuit with the commercial court.